Biomarkers for Diagnosing and Staging of Fabry Disease - Kramer, Johannes; Weidemann, Frank (Current Medicinal Chemistry, 2018)
Background: Fabry disease is an X-linked lysosomal storage disorder caused by deficient activity of α -galactosidase A which leads to progressive intracellular accumulation of globotriaosylceramide in tissues and organs including heart, kidney, vascular endothelium, the nervous system, the eyes and the skin. Cardiac involvement is common, leads to fatal complications and is mainly responsible for reduced life expectancy in Fabry disease. The exact staging of disease progression and timely initiation of treatment is essential in Fabry disease. Therefore, it is essential to use the possibilities of specific biomarkers for early detection of organ involvement or early diagnosis. Methods: By the use of Pubmed all relevant papers for biomarkers in Fabry disease were screened. The quality of retrieved papers was appraised using standard tools. Finally, 70 peer reviewed paper were included. Results: In the past biomarkers for Fabry disease biomarkers did not have clinical relevance. Nowadays, a lot of research is focusing on identification of new biomarkers and their clinical relevance. Only two biomarkers reached clinical applicability. Lyso-GB3 for identification of atypical FD variants and hsTNT for identification of cardiac involvement, which should indicate further diagnostics. Treatment response to ERT can be monitored by lyso-GB3 but data for long-time outcome are missing. A lot of GB3-related analogs are identified in urine and plasma, some of which might play an important role for managing Fabry disease in future. Conclusion: In conclusion, we suggest to measure lyso-GB3 and hsTNT at least once a year. The routine measurement of these two biomarkers will help now for the staging of every individual patient and in addition, will help for a better general understanding of Fabry disease.
Keywords: fabry disease diagnosis